Collaborators with the NKVD in the Prisoner-of-War Camp at Kozelsk - JACZYŃSKI, Stanisław (Historia i Świat, 2021)
The document refers to Polish officers seized by the NKVD authorities in the summer of 1940 from internment camps in Lithuania and Latvia and imprisoned in the Kozelsk camp. The prisoners were subjected to massive indoctrination aimed at changing their ideological and political attitudes and recruiting from amongst them secret collaborators (confidants). Several dozens of Polish officers of lower ranks with leftist views started to cooperate, to varying degrees, with the Soviet authorities. They advocated close military and political cooperation with the USSR. They were ostracised by a vast majority of prisoners of war who remained faithful to their military oath.